Kegiatan Ekstrakurikuler Mewarnai dalam Mengembangkan Kreativitas Siswa Kelas I MIN 2 Kota Palangka Raya - Isnaini Nurul Istiqomah; Yuliyatin Yuliyatin; Istiyati Mahmudah (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to describe coloring extracurricular activities in developing the creativity of grade I Min 2 students in Palangka Raya City. The method used in this study is a descriptive qualitative data collection tool in the form of interviews. The results obtained in this study were that the coloring extracurricular activities which were attended by grade I students and carried out every Saturday at MIN 2 Palangka Raya City were quite effective in increasing creativity and also training students' imaginations.